Spatial Theory and the Study of Religion - Knott, Kim (Religion compass, 2008)
A ‘spatial turn’ has been witnessed in the humanities and social sciences since Henri Lefebvre's La production de l’espace, and its translation into English in 1991. Subsequently, the socio-spatial theories of Lefebvre, Foucault, Certeau and postmodern geographers, such as Soja, Massey and Harvey, have had an impact on research in many disciplines, including religious studies. With its own traditions, of geography of religion and sacred space, it contributes theorists of its own, including van der Leeuw, Eliade, J. Z. Smith and Anttonen, but to these must be added those from beyond the boundaries of the discipline whose ideas have been formative for recent methodological and theoretical work by scholars such as Knott and Tweed. The article ends by asking what spatial theory contributes to the study of religion.